Associative nitrogen fixation linked with three perennial bioenergy grasses in field and greenhouse experiments. Issue 12 (19th October 2020) - Wewalwela, Jayani J.; Tian, Yuan; Donaldson, Janet R.; Baldwin, Brian S.; Varco, Jac J.; Rushing, Brett; Lu, Haoliang; Williams, Mark A.
Abstract: Associative nitrogen (N2 )‐fixation (ANF) by bacteria in the root‐zone of perennial bioenergy grasses has the potential to replace or supplement N fertilizer and support sustainable production of biomass, but its application in marginal ecosystems requires further evaluation. In this study, we first combined both greenhouse and field experiments, to explore the N2 fixation effects of three temperate feedstocks Miscanthus × giganteus (giant miscanthus, Freedom), Panicum virgatum (switchgrass, Alamo), and Saccharum sp. (energycane, Ho 02‐147). In field studies across three growing seasons, plant and soil pools of candidate feedstocks were partially composed of N derived from the atmosphere (Ndfa). Energycane, giant miscanthus, and switchgrass were estimated to derive >30%, %Ndfa. Greenhouse studies were also performed to trace isotopically labeled 15 N2 into plant biomass and soil pools. Evidence for Ndfa was detected in all three feedstock grasses (using reference 15 N of soil, chicory, and sorghum, δ 15 N +7.0). Isotopically labeled 15 N2 was traced into biomass (during grass elongation stage) and soil pools. Extrapolation of rates during the 24 hr labeling period to 50 days estimated 30%–55% of plant Ndfa, with the greatest Ndfa for energycane. The findings of the field natural abundance and greenhouse 15 N2 feeding experiments provided complementary evidence that perennial bioenergy grasses have the potential to support relatively high rates of ANF, and accumulate diazotroph‐derived N into biomass when grown on non‐fertilized soil. Abstract : Associative nitrogen (N2 )‐fixation by bacteria in the root‐zone of perennial bioenergy grasses have the potential to replace or supplement nitrogen fertilizer and support sustainable production of feedstock biomass. A 3 year field 15 N natural abundance and a greenhouse enriched 15 N feeding experiment were conducted to assess the possibility of bacterial supply of atmospheric nitrogen to feedstock grasses. It was shown that temperate bioenergy grasses switchgrass, miscanthus, and energycane can attain 30%–50% of nitrogen from atmospheric N2 via bacterial diazotrophs.